Secondary antifungal prophylaxis in allogeneic hematopoietic stem cell transplant recipients with invasive fungal infection - Mehmet S Pepeler; Şeyma Yildiz; Zeynep A Yegin; Zübeyde N Özkurt; Özlem G Tunçcan; Gonca Erbaş; Nurdan Köktürk; Ayşe Kalkanci; Zeki Yildirim (Journal of Infection in Developing Countries)
Introduction: Invasive fungal infection (IFI) is a major cause of morbidity and mortality in allogeneic hematopoietic stem cell transplantation (allo-HSCT) recipients. A previous history of IFI is not an absolute contraindication for allo-HSCT, particularly in the era of secondary antifungal prophylaxis (SAP). Prompt diagnosis and therapy are essential for HSCT outcome.